Heroes like us two stories - Raúf, Onjali Q. 1981- (Delacorte Press, 2022)
Two stories featuring ten-year old Ahmet, the Most Famous Refugee Boy in the World, and his friends, who stood up for Ahmet, and other refugee children like him, in Britain
2211
Keywords: Refugees / Juvenile fiction; Friendship / Juvenile fiction; Syrians / England / London / Juvenile fiction; London (England) / Juvenile fiction; England / Juvenile fiction; Refugees / Fiction; Friendship / Fiction; Syrians / England / London / Fiction; London (England) / Fiction; England / Fiction; Réfugiés / Romans, nouvelles, etc. pour la jeunesse; Amitié / Romans, nouvelles, etc. pour la jeunesse; Syriens / Angleterre / Londres / Romans, nouvelles, etc. pour la jeunesse; Angleterre / Romans, nouvelles, etc. pour la jeunesse; Syrians; Friendship; Refugees; England / London; England; Fictional Work; Juvenile works; Fiction; Romans; Kinderbuch